Kinetic Modulation of Pulsed Chronopotentiometric Polymeric Membrane Ion Sensors by Polyelectrolyte Multilayers - Xu, Y.; Xu, C.; Shvarev, A.; Becker, Thomas; De Marco, Roland; Bakker, Eric (American Chemical Society, 2007)
Polymeric membrane ion-selective electrodes are normally interrogated by zero current potentiometry, and their selectivity is understood to be primarily dependent on an extraction/ion-exchange equilibrium between the aqueous sample and polymeric membrane. If concentration gradients in the contacting diffusion layers are insubstantial, the membrane response is thought to be rather independent of kinetic processes such as surface blocking effects. In this work, the surface of calciumselective polymeric ion-selective electrodes is coated with polyelectrolyte multilayers as evidenced by potential measurements, atomic force microscopy, and electrochemical impedance spectroscopy. Indeed, such multilayers have no effect on their potentiometric response if the membranes are formulated in a traditional manner, containing a lipophilic ion exchanger and a calciumselective ionophore. However, drastic changes in the potential response are observed if the membranes are operated in a recently introduced kinetic mode using pulsed chronopotentiometry. The results suggest that the assembled nanostructured multilayers drastically alter the kinetics of ion transport to the sensing membrane, making use of the effect that polyelectrolyte multilayers have different permeabilities toward ions with different valences. The results have implications to the design of chemically selective ion sensors since surface-localized kinetic limitations can now be used as an additional dimension to tune the operational ion selectivity.